2017
DOI: 10.1007/s10517-017-3940-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sertoli and Leydig Cells in the Regulation of Spermatogonial Stem Cell and Development of Reproductive Disorders in Male C57Bl/6 Mice with Type 1 Diabetes Mellitus

Abstract: Course administration streptozotocin to male C57Bl/6 mice induces a complex of symptoms typical of type 1 diabetes mellitus: hyperglycemia and insulin deficiency, focal inflammatory infiltration of the pancreas, destructive changes in the Langerhans islets, damage to the insular apparatus (reduced number of PDX1 cells and insulin expression by the secreting cells). Male reproductive disorder are serious complications of type 1 diabetes mellitus. In "diabetic" mice, interstitial edema with inflammatory infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Disturbance of these regulatory factors may explain male infertility induced due to diabetes since spermatogenesis is supported by Sertoli cell growth factors and transcription factors 12 . A disturbance of testosterone synthesis by Leydig cells in testicular interstitial tissue are also disordered in diabetic testis 13 . In the fetal mouse testis, both Sertoli and Leydig cells are required for testosterone synthesis, while the adult Leydig cells synthesize testosterone to maintain male reproductive function 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance of these regulatory factors may explain male infertility induced due to diabetes since spermatogenesis is supported by Sertoli cell growth factors and transcription factors 12 . A disturbance of testosterone synthesis by Leydig cells in testicular interstitial tissue are also disordered in diabetic testis 13 . In the fetal mouse testis, both Sertoli and Leydig cells are required for testosterone synthesis, while the adult Leydig cells synthesize testosterone to maintain male reproductive function 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, targeting endothelial dysfunction may be a more effective treatment for ED. Studies have suggested that endothelial dysfunction may be alleviated by inhibiting autophagy (Altabas & Altabas, 2015;Verma & Anderson, 2002). Autophagy is a multi-step collaborative process regulated by autophagy-related genes (Sarkar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of ED is mainly vascular, caused by nitric oxide (NO) metabolism disorder in the cells. NO enhancing drugs like phosphodiesterase 5 inhibitors (PDE-5i), which alleviate NO's decay, are widely utilized but still fail sometimes (Altabas & Altabas, 2015). The dysfunction of endothelial cells (ECs) plays a vital role in the pathophysiological process of ED.…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in Quantity Most of the studies have reported that acute exposure to high levels of glucose under diabetic condition decreases the number of various types of stem cells, leading to insufficiency of stem cells used for repair and regeneration, which strongly relates to different diabetic complications (Keats and Khan, 2012;Skurikhin et al, 2017).…”
Section: Stem Cells Quantity Alteration In Diabetesmentioning
confidence: 99%